2007
DOI: 10.1007/s10456-007-9086-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression analysis of tubule forming and non-tubule forming endothelial cells: CDC42GAP as a counter-regulator in tubule formation

Abstract: The formation of new tubular structures from a quiescent endothelial lining is one of the hallmarks of sprouting angiogenesis. This process can be mimicked in vitro by inducing capillary-like tubular structures in a three-dimensional (3D) fibrin matrix. We aimed to analyze the differential mRNA expression in two phenotypically distinct cell populations from the same culture, namely in tubule-forming endothelial cells and monolayer endothelial cells not participating in tubule formation. A fibrin-rich 3D matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Consistent with this, recent evidence demonstrated that overexpression of Cdc42 GTPase activating protein (Cdc42 GAP), a protein which catalyzes GTP hydrolyzation and consequently decreases the active conformation of Cdc42, attenuates EC lumen formation while siRNA knockdown of Cdc42 GAP increased lumenogenesis 160 . In vitro , ECs with lower levels of Cdc42 GAP expression have been shown to be more likely to form tubes and lumens in comparison to ECs with a higher level of expression 160. Although the exact mechanistic role of Cdc42 in EC lumen formation is still unclear, this and other downstream GTPase pathway proteins demonstrate potentially promising therapeutic targets for pro or anti-angiogenesis therapies 161…”
Section: Molecular Mediators Of Angiogenesismentioning
confidence: 61%
“…Consistent with this, recent evidence demonstrated that overexpression of Cdc42 GTPase activating protein (Cdc42 GAP), a protein which catalyzes GTP hydrolyzation and consequently decreases the active conformation of Cdc42, attenuates EC lumen formation while siRNA knockdown of Cdc42 GAP increased lumenogenesis 160 . In vitro , ECs with lower levels of Cdc42 GAP expression have been shown to be more likely to form tubes and lumens in comparison to ECs with a higher level of expression 160. Although the exact mechanistic role of Cdc42 in EC lumen formation is still unclear, this and other downstream GTPase pathway proteins demonstrate potentially promising therapeutic targets for pro or anti-angiogenesis therapies 161…”
Section: Molecular Mediators Of Angiogenesismentioning
confidence: 61%
“…The few survivors experience premature aging associated with heightened genomic instability [36]. In vitro evidence suggests cdc42GAP1 negatively modulates angiogenesis [37]. Although it is expressed ubiquitously in mammals, it is predominantly expressed in the developing vasculature and heart in zebrafish at the stage examined here (Figure 3B).…”
Section: Resultsmentioning
confidence: 84%
“…The vesicles deliver Cdc42GAP, which then deactivates Cdc42 and thereby terminates further delivery of the vesicles and Cdc42GAP. Preliminary results from our laboratory suggest that this regulatory circuit might also control endothelial cell functions known to be instrumental in angiogenesis-like migration of endothelial cells and the formation of anastomoses between nascent endothelial cell tubules (Engelse et al, 2008;Koh et al, 2008Koh et al, , 2009.…”
Section: Discussionmentioning
confidence: 98%